Insufficiency in functional genomics studies, data, and applications: A case study of bio-prospecting research in ruminant microbiome - Rabapane, Kgodiso J.; Ijoma, Grace N.; Matambo, Tonderayi S. (Frontiers in Genetics, 2022)
Over the last two decades, biotechnology has advanced at a rapid pace, propelled by the incorporation of bio-products into various aspects of pharmaceuticals, industry, and the environment. These developments have sparked interest in the bioprospecting of microorganisms and their products in a variety of niche environments. Furthermore, the use of omics technologies has greatly aided our analyses of environmental samples by elucidating the microbial ecological framework, biochemical pathways, and bio-products. However, the more often overemphasis on taxonomic identification in most research publications, as well as the data associated with such studies, is detrimental to immediate industrial and commercial applications. This review identifies several factors that contribute to the complexity of sequence data analysis as potential barriers to the pragmatic application of functional genomics, utilizing recent research on ruminants to demonstrate these limitations in the hopes of broadening our horizons and drawing attention to this gap in bioprospecting studies for other niche environments as well. The review also aims to emphasize the importance of routinely incorporating functional genomics into environmental metagenomics analyses in order to improve solutions that drive rapid industrial biocatalysis developments from derived outputs with the aim of achieving potential benefits in energy-use reduction and environmental considerations for current and future applications.